2023
DOI: 10.1007/s12528-023-09356-3
|View full text |Cite
|
Sign up to set email alerts
|

Adopting distributed pair programming as an effective team learning activity: a systematic review

Abstract: As online learning has become an inevitable trend in the post-peak era of the COVID-19 pandemic, distributed pair programming (DPP) is gaining momentum in both education and industry. DDP serves as a collaborative programming approach and also benefits the development of computational thinking, a fundamental skill in today’s world. This study conducted a systematic review of studies on DPP published after 2010 to understand the themes and factors that impact the team effectiveness of DPP and thus inform future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…both in the prospect of securing future employment and in the desire to acquire the skills necessary for roles driven by Generative Artificial Intelligence, as confirmed by the study by Kelly, Sullivan, and Strampel (2023). These results offer an overview of three key areas: learning outcomes (Bower et al 2024), pedagogy (Xu & Correia, 2023), and evaluation (Kiryakova & Angelova, 2023).…”
Section: Iberoamerican Journal Of Science Measurement and Communicationmentioning
confidence: 98%
“…both in the prospect of securing future employment and in the desire to acquire the skills necessary for roles driven by Generative Artificial Intelligence, as confirmed by the study by Kelly, Sullivan, and Strampel (2023). These results offer an overview of three key areas: learning outcomes (Bower et al 2024), pedagogy (Xu & Correia, 2023), and evaluation (Kiryakova & Angelova, 2023).…”
Section: Iberoamerican Journal Of Science Measurement and Communicationmentioning
confidence: 98%
“…PP is an active learning methodology that compares pair programming and solo programming. Its effectiveness is affected by compatibility factors such as students' skills, personality, and self-esteem (Xu and Correia, 2023). TBL develops critical thinking skills and problemsolving ability to solve problems individually and empowers students to solve complex issues (Sibley and Ostafichuk, 2023).…”
Section: Sq1 Which Alms Were Addressed In the Publications?mentioning
confidence: 99%
“…Xu and Correia (2023) conducted a systematic review of DPP studies published after 2010 to understand the issues and factors that impact the effectiveness of the DPP team. 36 The results showed that individual characteristics such as previous programming experience, actual and perceived ability, gender, personality, time management, confidence, and self-esteem had been the subject of significant research. Regardless of the investigations, studies focused on specifically analyzing random and systematic errors concerning the problem posed have yet to be found.…”
Section: Introductionmentioning
confidence: 99%